Sertãovida em cena: a busca por um solo poético caipira e sertanejo - Costa, Diogo Ramon da Silva (2022)
The related research provided the production of knowledge during the artistic-scientific process, which may influence new questions and future practices, in the same way that it left an artistic record that expands the continuous process of knowledge in the performing arts. The present work results from a research that was developed from mid-2019 to the end of 2021, composing the line of research: Poetics and Aesthetics of the Performing Arts of the Graduate Program in Performing Arts (Pós-Graduação em Artes da Cena – PPGAC) of the School of Music and Performing Arts (Escola de Música e Artes Cênicas – EMAC) of the Federal University of Goiás (Universidade Federal de Goiás – UFG), being linked to the following laboratories: Laboratory of Scenic Assembly and Theater Education (LabMonTe / EMAC / UFG), Costume Creation Laboratory, Collection of Costumes and Sewing Atelier (Laboratório de Montagens Cênicas e Teatro Educação – LabCriaa/ EMAC/ UFG), and the Interdisciplinary Laboratory for Research in Performing Arts (Laboratório Interdisciplinar de Pesquisa em Artes da Cena – Lapiac) linked to EMAC and the Faculty of Physical Education and Dance (Faculdade de Educação Física e Dança – FEFD/UFG). The dissertation receives the title of SertãoVida em cena: The search for a rustic and sertanejo poetic soil (SerTãoVida em cena: A busca por um solo poético caipira e sertanejo) and registers the investigation about the relations between the sertão and the scene, taking into account the particularities of the caipira and sertaneja culture and the specifics of the scene in its contemporaneity. The guiding question that guides this investigative and creative process is: Through the study and experience with the concept of 'sertão', 'caipira' and 'sertanejo'; how and what incitements, inspirations and poetics can be provoked for artistic creation? The main objective of the investigation was to research and experience country and country experiences as a scenic inspiration in the search for a poetic soil, that is, a scenic product that would dialogue with the atmosphere of the backwoods. The work created was the audiovisual and theatrical solo Sertão, Sol & Canção, which is divided into the following three microscenes: Bendito, Vaquinha and Encantado. From a methodological point of view, the development of the written work was supported by the methodological dimensions of self-ethnography and action research, among other procedures of methodologies in the artistic field which supported the creative proposal of the project. In this investigative walk, new actions for the encounter with the sertão were being tried, which go beyond the proposal of face-to-face interaction with communities and groups of caipiras and sertanejos, as is the example of the poetic encounter with the sertão through social isolation. The artistic work created, shared through a video platform, is an artistic product that explains the studies and experiments carried out during the investigation, as well as promotes the writing of some records of this dissertation work. The related research provided the production of knowledge during the artistic-scientific process, which may influence new questions and future practices, in the same way that it left an artistic record that expands the continuous process of knowledge in the performing arts.